Creativity in Teaching Nature and Society - Ajdina Župić; Hana Hodžić; Merjem Sušić (Društvene i Humanističke Studije, 2023)
The main goal of this paper is to point out the concept of creativity in teaching, specifically creativity in the teaching of Nature and Society. Nature and society, as a subject, provide many opportunities to express the creativity that we carry within us through the role of a teacher, as well as to teach students how to be creative. The paper highlights examples of different teaching units that indicate ways to encourage creativity in students and awaken their imagination. Through teaching, through tasks that the teacher creatively devises, we encourage students to think creatively and act, in addition to acquiring knowledge more permanently and functionally. Possibilities of creating Nature and Society lessons through creative examples and experiments, as well as evaluating and measuring creativity, were presented. The work results indicated that creative teachers create their fruits, which are called creative students, that they are causally connected, and that creativity is a synonym for an expert and professional teacher.